Advanced Microwave Imaging - Ahmed, Sherif Sayed; Schießl, Andreas; Gumbmann, Frank; Tiebout, Marc; Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (IEEE Microwave Magazine, 2012)
Due to the enormous advances made in semiconductor technology over the last few years, high integration densities with moderate costs are achievable even in the millimeter-wave (mm-wave) range and beyond, which encourage the development of imaging systems with a high number of channels. The mm-wave range lies between 30 and 300 GHz, with corresponding wavelengths between 10 and 1 mm. While imaging objects with signals of a few millimeters in wavelength, many optically opaque objects appear transparent, making mm-wave imaging attractive for a wide variety of commercial and scientific applications like nondestructive testing (NDT), material characterization, security scanning, and medical screening. The spatial resolution in lateral and range directions as well as the image dynamic range offered by an imaging system are considered the main measures of performance. With the availability of more channels combined with the powerful digital signal processing (DSP) capabilities of modern computers, the performance of mm-wave imaging systems is advancing rapidl
lhft_intern.bib::Ahmed2012c

A novel active real-time digital-beamforming imager for personnel screening - Ahmed, S. S.; Schießl, Andreas; Schmidt, Lorenz-Peter (EUSAR 2012, 2012)
Personnel screening is an essential requirement nowadays for securing air traffic as well as critical infrastructures. Several passive and active imaging systems based on millimeter wave technologies were developed to address the demanded security needs. A novel active near-field imager based on two-dimensional sparse array architecture combined with digital-beamforming technique is demonstrated here. The system is fully electronic, and hence operates in real-time to deliver fully focused three-dimensional images of high dynamic range and resolution. A 2 m times 1 m imager is built and demonstrated full agreement with the theoretical design. The imaging concept, measurement technique, and various imaging results are presented.
lhft_intern.bib::Ahmed2012a

A Technology Demonstrator for a 0.5 m x 0.5m Fully Electronic Digital Beamforming mm-Wave Imaging System - Schießl, Andreas; Ahmed, S. S.; Genghammer, A.; Schmidt, Lorenz-Peter (EuCAP 2011, 2011)
This paper describes a demonstrator for a millimeter-wave imaging system, showing for the first time the feasibility of an active fully electronic imaging system in the 80 GHz region using a 2D planar sparse array as an imaging sensor. The demonstrator is capable of capturing images of living persons. In this work, the requirements regarding measurement speed are derived. The system architecture is described in detail using block diagrams. The reference channel concept, the signal distribution network, the modular architecture and the ADC / signal processing concepts are explained. Selected measurement results of key system parameters are presented. mm-Wave images of living persons are shown, including examples demonstrating the effects of movement during the measurement.
lhft_intern.bib::Schiessl11a

Data Statistics and Image Properties of a Large Multistatic mm-Wave Imaging System - Schießl, Andreas; Ahmed, S. S.; Schmidt, Lorenz-Peter (14th International Radar Symposium IRS2013, 2013)
Near field radar systems offer potential solutions for security and non-destructive testing appplications. This work presents the system architecture of a fully electronic multistatic mm-wave imager at E-band. The measurement and processing chain of the imaging system is reviewed along with the corresponding data statistics. Reconstructed data of a complex test pattern with specific 3D elements is used to demonstrate the high imaging performance of the system. © 2013 German Inst of Navigation.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.datast

Differential Excitation of a Hybrid Antenna for a 75 GHz Antenna Array Implemented on a Multilayer PC Board - Juenemann, R.; Zielska, A.; Schießl, Andreas; Methfessel, Sebastian Dirk; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
If, for practical reasons, there is a need to bend a differential waveguide, the bend has to be compensated to avoid mode conversion into the common mode which can lead to unwanted resonance effects. This paper deals with two possible compensating structures for a 45° bend in a differential waveguide exciting a hybrid antenna. The hybrid antenna in turn is part of a large array used in a security scanner for people screening. Simulations show antenna behavior with and without compensation with respect to matching, mode conversion, gain, and suppression of the cross polarization. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.differ
Keywords: antenna feed; differential amplifier; horn antenna; microwave imaging; mode conversion

Fast Multistatic Measurement System for Short Range Imaging Radar Development - Schießl, Andreas; Ahmed, S. S.; Genghammer, A.; Schmidt, Lorenz-Peter (12th URSI Commission-F Triennial Open Symposium on Radio Wave Propagation and Remote Sensing, 2011)
lhft_intern.bib::Schiessl11

Fully Electronic Active E-Band Personnel Imager with 2 m^2 Aperture - Ahmed, Sherif Sayed; Genghammer, Andreas; Schießl, Andreas; Schmidt, Lorenz-Peter (IEEE MTT-S International Microwave Symposium 2012 (IMS 2012), 2012)
The demand on advanced personnel screening systems led to the development of several active and passive imagers. Among them, active multistatic imaging ensures high image quality and allows fully electronic screening. An active E-band imager is introduced in this paper, which operates in real-time and delivers images of 30-dB dynamic range. Imaging of humans is achieved by optimizing the acquisition time using a dedicated digital signal processing solutio
lhft_intern.bib::Ahmed2012b

Increasing Measurement Speed in mm-Wave Imaging Systems by Means of Frequency Multiplexing - Koeppel, Tobias; Methfessel, Sebastian Dirk; Schießl, Andreas; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
Target movement during illumination causes reliability issues in imaging systems, particularly in applications where time efficiency is needed. A technique is proposed in order to reduce measurement time and as a consequence also motion blur effects. With the use of OFDM waveforms, a decrease in measurement time by a factor of 1.6 is achieved with minimal hardware costs. Measurement time for increasing numbers of carriers is predicted. A hardware realization is investigated with respect to hardware imperfections. Influence of intermodulation distortion and phase noise on dynamic range is discussed. Afterwards, imaging results are presented. © 2013 EMA.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.increa
Keywords: microwave imaging; multistatic radar; signal processing; sparse array

Multistatic mm-Wave Imaging with Planar 2D-Arrays - Ahmed, S. S.; Schießl, Andreas; Schmidt, Lorenz-Peter (GeMiC 2009, 16 - 18 March, München, Germany, 2009)
This work reports measurement results for the scanning of 2D and 3D objects in W-band (75 to 110 GHz) using active 2D planar arrays in multistatic configuration with digital beamforming technique. The image quality of the object reflectivity depends mainly on the frequency band, array configuration, signal polarization, and focusing method. Multistatic measurements allow for higher dynamic range, reduced antennas count and the feasibility for cross-polarization measurements. Measurements meet the theoretical expectation and the simulation results down to 4 mm resolution. Two multistatic arrays will be presented and compared in terms of image resolution, antennas count, SNR and digital processing needed.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.multis
Keywords: Back-propagation; Digital beamforming; Imaging; Mm-wave; Point spread function; Signal to noise ratio

Near Field mm-Wave Imaging with Multistatic Sparse 2 D-Arrays - Ahmed, S. S.; Schießl, Andreas; Schmidt, Lorenz-Peter (Proceedings of the 6th European Radar Conference, 2009)
A near field application of multistatic 2D sparse arrays designed based on an effective aperture concept is presented. Several test arrays which utilize this concept are introduced along with simulation and measurement results for near field operation at 100 GHz. High reduction in the needed number of transmit and receive modules is verified along with the drawbacks in the image quality. Good agreement between measurements and simulations is demonstrated.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.LEH.nearfi

Novel Fully Electronic Active Real-Time Millimeter-Wave Imaging System based on a Planar Multistatic Sparse Array - Ahmed, Sherif Sayed; Schießl, Andreas; Schmidt, Lorenz-Peter (International Microwave Symposium 2011, 2011)
The interest on active millimeter-wave and microwave imaging systems is increasing nowadays due to their utilization in security, medical, and industrial applications. Imaging systems using monostatic arrays suffer from the high number of antenna positions, making a fully electronic solution very costly and impractical. Multistatic arrays, however, offer the chance for high reduction factors in the number of antennas, and then allow for fully electronic solutions. Here, a new array architecture is presented, which is suitable for real-time operation and is capable of delivering high image quality in means of resolution and dynamic range. An example array is demonstrated for operation from 72 to 80 GHz. The imaging system hardware is introduced, along with imaging results of human
lhft_intern.bib::Ahmed11

Phase Error Sensitivity in Multistatic Microwave Imaging Systems - Schießl, Andreas; Ahmed, S. S.; Genghammer, A.; Schmidt, Lorenz-Peter (43th European Microwave Week, 2013)
Current digital-beamforming multistatic mm-wave array designs show superior near field imaging performance. Therefore, mm-wave imaging systems based on these concepts are suitable for a variety of security, medical and industrial applications. The theoretically achieved array performance can be degraded by noise and unwanted signals within the actually implemented systems. In this work, the sensitivity of such systems on certain types of systematic errors within its signal processing chain including the system error correction mechanism is discussed and analyzed. Effects of errors within the reconstructed images are demonstrated, and methods to reduce the effects of some dominant error signals are proposed. © 2013 EMA.
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.phasee
Keywords: error correction; microwave imaging; multistatic radar; signal processing

Temperature Sensitivity of Large Digital-Beamforming Multistatic mm-Wave Imaging Systems - Schießl, Andreas; Ahmed, Sherif Sayed; Genghammer, Andreas; Schmidt, Lorenz-Peter (IEEE International Microwave Symposium 2013, 2013)
Large multistatic mm-wave imaging systems have recently been developed and proved to be efficient for security applications. This work analyzes the effects caused by temperature changes on the imaging performance of a state-of-the-art system. The temperature dependent phase drift of a single measurement channel is characterized. A linearized model for the phase drifts in the RF channels is thus derived This model is applied to simulate for systematic phase drifts in the recorded raw data of the imaging system at different temperature profiles. Afterwards, images are reconstructed using modified raw data. Accordingly, the degradation in the imaging performance due to temperature changes is presented in terms of image quality and the associated point spread functions. © 2013 IEE
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.LEH.temper
Keywords: Chip-on-board; Microwave imaging; Millimeter wave technology; Multichip modules; Temperature dependence